Elementos a considerar para el bienestar animal durante el transporte vehicular terrestre de ganado bovino: Revisión bibliográfica (2021)
In Colombia, due to the fact that the cattle production systems are withdrawn from the facilities arranged for the slaughter of animals, they need to be transported by land from these production areas to the processing plants, which leads these animals to challenge long periods of travel in which different conditions or negative factors that generate stress influence them, thus affecting the welfare and animal health, quantity and safety of the meat, and as a result for all these purposes there is a great economic loss for the meat industry.